Anticancer activity of Ilex khasiana, a rare and endemic species of holly in Northeast India, against murine lymphoma - Charles Lalnunfela; Pawi Bawitlung Lalthanpuii; Hmar Tlawmte Lalremsanga; Zothansiama; Chhaihlo Lalmuansangi; Mary Zosangzuali; Nachimuthu Senthil Kumar; Tochhawng Lalhriatpuii; Kholhring Lalchhandama (Heliyon)
Ilex khasiana Purkay. is a lesser-known species of holly (family Aquifoliaceae) that is endemic to Northeast India. Designated as critically endangered, the plant is used in the treatments of bacterial infections, cancer, intestinal helminthiasis, tuberculosis, and viral infections. A methanol extract of the leaves was prepared from which 16 different compounds were identified using gas chromatography-mass spectroscopy. An alkylated phenol, 2,6-di-tert-butylphenol, was the predominant compound. Acute toxicity test indicated that the plant extract was non-toxic even at the highest dosage tested, i.e., 2000 mg/kg body weight. The plant extract caused considerable prolongation of survival in mice transplanted with Dalton's lymphoma ascites, extending life by 33 %, with median survival time of 35.5 and average survival time of 22.83 days, and with a treatment to control ratio of 131.37 %. Reduction of body mass, lipid peroxidation, alanine transaminase, aspartate aminotransferase, and creatinine were seen in DLA-transplanted mice after treatment with the plant extract. On the other hand, glutathione level, glutathione S-transferase and superoxide dismutase activity increased. Alkaline comet assay showed that the plant extract effectively induced DNA damage, producing a tail length of 11.89 μm and Olive moment of 2.36 at 250 mg/kg bwt, the most effective dosage. Molecular docking revealed high ligand binding ability of 2,6-di-tert-butylphenol to chemokine receptor CXCR4, DNA topoisomerase 2-alpha, DNA topoisomerase 2-beta, histone deacetylases (HDAC1, HDAC2, HDAC3), Janus kinase 1 and programmed cell death protein 1. The safety and anticancer activity in the present study substantiate the therapeutic importance of I. khasiana as acclaimed in the Mizo traditional medicine. Additionally, the study advocates further pharmacological investigations as well as the conservation and propagation of the endangered plant for future research.